A chemo-damage-transport model for chloride ions diffusion in cement-based materials: Combined effects of sulfate attack and temperature. (21st June 2021) - Wang, Penggang; Mo, Rui; Li, Sen; Xu, Jun; Jin, Zuquan; Zhao, Tiejun; Wang, Dezhi
Highlights: Formation of Friedel's salt leads to porosity changes and cracking of cement matrix. Effects of sulfate attack and temperature on chloride transport in cement-based materials were simulated. Chloride distribution and quantity evolution of expansion products were quantified numerically. Abstract: Corrosion of reinforcement caused by chloride penetration has become the primary factor of concrete durability in the saline soil environment. A chemo-damage-transport model for chloride diffusion is studied, in which the effects of sulfate attack and temperature on chloride diffusivity in concrete are taken into consideration. Specifically, the volume changes of Friedel's salt and ettringite can cause the expansion and cracking of cement-based materials. Meanwhile, temperature has a significant influence on the reactions rates, mass transfer and ions diffusivity. The model is validated by published experimental results. The main conclusion is that there exists a peak value of the bound chloride ions. Near the exposed surface of the samples, the bound chloride content decreases with the increase of temperature. For the peak corresponding position and inward part, with the temperature rises, the bound chloride content in cement-based materials increases obviously.